Peran Program Kampus Merdeka terhadap Peningkatan Kualitas Mahasiswa - Sabrina Widya Vernanda; Desy Safitri; Sujarwo (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
This independent campus is a new policy which will bring changes in education so that it becomes freer with an innovative learning culture. The programs offered by the independent campus are very diverse, adapting to the needs of each student and university. This research aims to determine changes in the quality and skills of students who join the independent campus program. The research method used is a qualitative research method with a literature research type. Data collection in this research uses documentation study techniques by analyzing the contents of previous documents or journals that are relevant to the topic being studied. The data sources in this study are various books and journals. The research results show that the implementation of the independent campus program is effective in improving the quality of students in preparing themselves to enter the world of work. In the era of industrial revolution 5.0, student’s abilities must be further improved because competition will be increasingly fierce, so the MBKM program is very helpful.